Bureaucratic Reform to the improvement of public services Challenges for Indonesia - Yusri Adi (Publikauma : Jurnal Administrasi Publik Universitas Medan Area, 2018)
Many factors can affect the performance of the government bureaucracy, including the absence of meritocracy (using the best talent) caused, for example, the recruitment process which does not target all segments of society, elections and the progress of civil servants are not based on the capacity, knowledge and skills, in fair competition and open. This study addressed the issue of government bureaucracy in Indonesia, which is multidimensional and protracted as a vicious circle, and discusses how improved public service for good governance can create and utilize to get out of the vicious circle and deterioration in innovative ways. This study used a qualitative approach. Based on data collection techniques, data collection techniques used in this research is the study of the literature on the theory of Reinventing Government, which is considered as the main theory. Results from this study, to solve complex problems required comprehensive strategy consisting of three areas, namely, political leadership, harmonization of public policy (including rules and regulation), and free from corruption